Q/A on teaching credit classes for entrepreneurship research. Issue 3 (10th August 2015) - Watstein, Sarah Barbara; Scanlon, Mary G.; Cramer, Steve
Abstract : Purpose: – The purpose of this paper is to present the question and answer (Q/A) to provide an opportunity for two seasoned academic business librarians to share their experiences with courses in entrepreneurship in their universities. Design/methodology/approach: – Question and answer. Findings: – The evolving business school curricular landscape, and especially an increase in courses in entrepreneurship, presents unique opportunities for engagement, visibility and centrality for academic business librarians. Originality/value: – Entrepreneurship is increasingly valued in today's world. To be successful, entrepreneurs must successfully deal with and navigate a highly complex information landscape. Academic business librarians are positioned to help student, faculty and future entrepreneurs alike learn the skills to successfully traverse this landscape.